Goddess Vināyakī, the female Gaṇeśa - Agrawala, Prithvi Kumar (Indian civilisation series, 1978)
Study on the female form of Gaṇeśa, Hindu deity, with special reference to Sanskrit sacred literature and Hindu sculpturalfindings.